2021
DOI: 10.1016/j.iot.2019.100122
|View full text |Cite
|
Sign up to set email alerts
|

Cost-sensitive stacked auto-encoders for intrusion detection in the Internet of Things

Abstract: Intrusion Detection System (IDS) is an important tool for protecting the Internet of Things (IoT) networks against cyber-attacks. Traditional IDSs can only distinguish between normal and abnormal behaviors. On the other hand, modern techniques can identify the kind of attack so that the appropriate reactions can be carried out against each type of attack. However, these techniques always suffer from the class-imbalance which affects the performance of IDS. In this paper, we propose a cost-sensitive stacked aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…For example, in the IC_VAE model proposed by Lopez-Martin et al [48], using the NSL-KDD dataset, the types of attacks detected by this model are Probing, Remote to Local (R2L), User to Root (U2R), and Denial of Service (DoS) Attacks. Similarly, studies proposed by [13,18,36,44,47] detected the same types of attacks, using NSL-KDD and KDD Cup 1999 datasets. Moreover, in [15,38], by adapting the NSL-KDD and UNSW-NB15, they extended the range of attack by detecting modern attacks, such as Fuzzer and worm, back door, analysis, exploits, generic, seel-code, and recionnary.…”
Section: Analysis Of Type Of Attacks Detectedmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, in the IC_VAE model proposed by Lopez-Martin et al [48], using the NSL-KDD dataset, the types of attacks detected by this model are Probing, Remote to Local (R2L), User to Root (U2R), and Denial of Service (DoS) Attacks. Similarly, studies proposed by [13,18,36,44,47] detected the same types of attacks, using NSL-KDD and KDD Cup 1999 datasets. Moreover, in [15,38], by adapting the NSL-KDD and UNSW-NB15, they extended the range of attack by detecting modern attacks, such as Fuzzer and worm, back door, analysis, exploits, generic, seel-code, and recionnary.…”
Section: Analysis Of Type Of Attacks Detectedmentioning
confidence: 87%
“…We found that the trend goes to AE techniques. The studies [18,[41][42][43][44]48] used AE techniques because of the ability of AE to take advantage of the linear and nonlinear dimensionality reduction to detect the anomalies. The AE training phase involves the reconstruction of clean input data from a partially destroyed one as well as the ability of AE to deal with heterogeneity, unstructured and high dimensional data that generated from IoT device.…”
Section: Discussionmentioning
confidence: 99%
“…In another work, Telikani et al [ 106 ] proposed a CSSAE technique for intrusion detection, especially in IoT networks. The main focus of the paper is the class imbalance problem in the datasets, which tends to bias the results towards the majority class.…”
Section: Learning-based Solutions For Securing Iotmentioning
confidence: 99%
“…Consequently, some researchers have tried to solve this problem. Telikani and Gandomi suggested a cost-sensitive stacked auto-encoder (CSSAE) approach to handle the imbalance problem in IoT intrusion detection systems [53]. CSSAE produced a cost for each class that depends on the distribution of the classes.…”
Section: Related Workmentioning
confidence: 99%